Golden Gate - Bryndís Charlotte Sturludóttir 1990-; Petra Kristín Frantz 1991- (2020)
In this report we cover the project “Golden Gate” which is a B.Sc. final project at Reykjavík University, presented in May 2020. The project involves building a network tunnel between two remote regions for data transfer and cross-region replication. Lokaverkefni er trúnaðarmál, sjá 2020-05-15 02-17.pdf